IMPACT OF INFRASTRUCTURE DEVELOPMENT JALUR JALAN LINTAS SELATAN (JJLS) ON CHANGES IN LAND USE IN GADINGSARI VILLAGE, SANDEN DISTRICT, BANTUL REGENCY, YOGYAKARTA, INDONESIA - Hendry Edy; M. Baiquni; Bambang Triatmodjo (Geosfera Indonesia, 2019)
Infrastructure Development Jalur Jalan Lintas Selatan (JJLS) is a National program that passes through 5 provinces in Java, which is one of the provinces passed through the Special Region of Yogyakarta. One of the villages passed by the JJLS development in the Special Province of Yogyakarta is Gadingsari Village, Sanden District, Bantul Regency. In this study, it will be seen how changes in land use in Gadingsari village before and after JJLS. The purpose of this study was to analyze changes in land use that occurred in Gadingsari Village. The analytical method used is a qualitative descriptive analysis method. Changes in land use were obtained from the Satellite Image Overlay Analysis in the span of time, namely before JJLS was built in 2013 and after JJLS was built in 2017 and strengthened with field surveys and in-depth interviews. From the results of the research, it was found that the land area for settlements in Gadingsari Village before and after the JJLS had changed. Before the existence of JJLS residential area was 78.90 hectare and it expanded to 104.93 hectare after the construction of JJLS, there was an increase of around 32.99% . Key words: Infrastructure, Overlay, JJLS, Land References Ahardi Muhammad A., Sawitri S. & Abdi S. (2015). Pengaruh Perubahan Penggunaan Lahan Terhadap Perubahan Zona Nilai Tanah di Kecamatan Gayamsari Kota Semarang Tahun 2004 dan 2014Jurnal Geodesi Undip, 4(4), 316–324. Beatus M. Laka, Uca Sideng & Amal (2017). Perubahan Penggunaan Lahan di Kecamatan Sirimau Kota Ambon .Jurnal Geocelebes, 1(2), 43–52. Fadilla Restu , Sudarsono B. & Bashit N.(2018). Analisis Kesesuaian Perubahan Penggunaan Lahan Terhadap Rencana Tata Ruang/wilayah di Kecamatan Penjaringan kota Administratif Jakarta Utara Menggunakan Sistem informasi Geografis. Jurnal Geodesi Undip, 7(1), 109–119. Kubangun Siti Hadjar, Haridjaja O.&Gandasasmita K. (2016). Model Perubahan Penutupan / Penggunaan Lahan untuk Identifikasi Lahan Kritis di Kabupaten Bogor , Kabupaten Cianjur dan Kabupaten Sukabumi Majalah Ilmiah Globe, 18(1), 21–32. Kusumaningrat Merpati D., Sawitri Subiyanto&Yuwono B. D. (2017) Analisis Perubahan Penggunaan dan Pemanfaatan Lahan Terhadap Rencana Tata Ruang Wilayah tahun 2009 dan 2017 (Studi kasus : Kabupaten Boyolali). Jurnal Geodesi Undip, 3, 28–43. Murdaningsih, Widiatmaka, Munibah, L. & Ambarwulan, W. (2017). Analisis Spasial Perubahan Penggunaan Lahan Pertanian Di Kabupaten Indramayu. Majalah Ilmiah Globe, 19(2), 175–184. Nuraeni, R., Sitorus, S.R P. & Panuju, D.R. (2017). Analisis Perubahan Penggunaan Lahan dan Arahan Penggunaan Lahan Wilayah di Kabupaten Bandung. Buletin Tanah Dan Lahan, 1(1), 79–85. Sadewo M Nur, Imam B. (2018). Simulasi Perubahan Penggunaan Lahan Akibat Pembangunan Kawasan Industri Kendal (KIK) Berbasis Cellular Automata. Majalah Geografi Indonesia, 32(2), 115–122. https://doi.org/10.22146/mgi.33755 Wahyuni, S., Guchi, H., & Hidayat, B. (2014). Analisis Perubahan Penggunaan Lahan dan Penutupan Lahan Tahun 2003 dan 2013 di Kabupaten Dairi. Jurnal Online Agroekoteknologi, 2, 1310–1315. Wahyunto, M.Z. Abidin, A. Priyono &Sunaryo (2001). Studi Perubahan Penggunaan Lahan di Sub DAS Citarik, Jawa Barat dan DAS Kaligarang, Jawa Tengah. In Prosiding Seminar Nasional Multifungsi Lahan Sawah (pp. 39–40). Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License